2012
DOI: 10.1093/geronb/gbr162
|View full text |Cite
|
Sign up to set email alerts
|

Idea Density Measured in Late Life Predicts Subsequent Cognitive Trajectories: Implications for the Measurement of Cognitive Reserve

Abstract: Linguistic ability in young adulthood, as measured by ID, has been previously proposed as an index of neurocognitive development and/or cognitive reserve. The present study provides evidence that even when ID is measured in old age, it continues to be associated with subsequent cognitive decline and as such may continue to provide a marker of cognitive reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…It is noteworthy that this figure does not express a relation necessarily found between CR and these studied topics. At least in the last five years, researches on the Cognitive Reserve orbited around 7 topics: Cognitive Function [9][10][11][12][18][19][20][21][22]56 , Brain Structure 8,[27][28][29]35,37,39,42,47,49,58,59,65 , New Methods of Measure 36,48,50,60,66 , Life Habits [13][14][15][16][17]25,[30][31][32]34,43,46,52,64 , Life Events 44,45 , Cognitive Decline 26,33,38,40,41,51,…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that this figure does not express a relation necessarily found between CR and these studied topics. At least in the last five years, researches on the Cognitive Reserve orbited around 7 topics: Cognitive Function [9][10][11][12][18][19][20][21][22]56 , Brain Structure 8,[27][28][29]35,37,39,42,47,49,58,59,65 , New Methods of Measure 36,48,50,60,66 , Life Habits [13][14][15][16][17]25,[30][31][32]34,43,46,52,64 , Life Events 44,45 , Cognitive Decline 26,33,38,40,41,51,…”
Section: Resultsmentioning
confidence: 99%
“…Low scores on both tests indicate less idea generation than that of HOAs and support earlier findings of less idea density in written and oral narratives. This was the case with the young nuns in the study by Snowden et al (1996) and individuals with clinically diagnosed MCI in the studies of Farias et al (2012) and Mueller et al (2016).…”
Section: Concept Definition and Object Description Subtestsmentioning
confidence: 82%
“…In other adult language research, a number of studies have demonstrated relationships between PD in early adult life and cognition in late life (Engelman et al, 2010;Iacono et al, 2009;Kemper et al, 2001;Riley et al, 2005). Farias et al (2012) recently reported a significant association between low PD measured in late life and steeper subsequent declines in cognitive function. Many authors describe proposition density as an index of "cognitive reserve" or a buffer against the effects of neuropathology (Chand et al, 2012;Engelman et al, 2010;Iacono et al, 2009;Snowdon et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, propositional analyses have been done using written samples and oral samples, different types of oral-language sampling (e.g., interviews, story recall, picture description, filmstrip narration, personal narratives), different sample lengths, and different measurement techniques (e.g., total number of essential propositions, proposition complexity index, proposition density). Some studies of proposition density report the number of expressed propositions divided by the number of words (Brown, Snodgrass, & Covington, 2007;Bryant et al, 2013;Covington, 2007;Ferguson et al, 2013;Roark, Mitchell, Hosom, Hollingshead, & Kaye, 2011), whereas others report the number of ideas per 10 words Cunha, Sousa, Mansur, & Aluisio, 2015;Farias et al, 2012;Kemper, Greiner, Marquis, Prenovost, & Mitzner, 2001) and in some cases use just the last 10 sentences of the samples (Engelman, Agree, Meoni, & Klag, 2010;Riley, Snowdon, Desrosiers, & Markesbery, 2005;Snowdon et al, 1996). Comparisons of results across studies require careful consideration of all these possible variables, which can make it challenging to synthesize, replicate, and build on the findings.…”
mentioning
confidence: 99%